Perceptions and Experiences With Evidence-based Treatments Among People Who Use Opioids. Issue 2 (9th March 2023) - Carlberg-Racich, Suzanne; Sherrod, Darielle; Swope, Kristin; Brown, Dannielle; Afshar, Majid; Salisbury-Afshar, Elizabeth
Abstract : Objectives: Even where treatment is available, people who use drugs (PWUD) may not seek help. Few published studies examine beliefs, experiences, and perceptions of evidence-based treatment among PWUD who are not actively engaged in care. This study aimed to explore the experiences of PWUD in considering or accessing treatment and gauge receptiveness to low-threshold treatment models. Methods: A purposeful sample of participants actively using opioids and with previous interest in or experience with treatment was recruited from a harm reduction program in Chicago. Semistructured interviews were conducted to explore key phenomena while allowing for unanticipated themes. The instrument included questions about historical drug use, treatment experience, and perceptions of how to improve treatment access and services. Private interviews were audio recorded, transcribed, and double coded by 2 analysts. Queries of coded data were analyzed using issue-focused analysis to identify themes. Results: The sample (N = 40) approximated groups at highest risk of fatal overdose in Chicago, with more than 80% between the ages of 45 to 64 years, 65% African American, and 62% male identified. The majority had prior treatment experience, although all resumed use after completing or leaving treatment. The most prevalent barriers to treatment included structural barriers related to social determinants, lack of readiness for abstinence, burdensome intake procedures, and regulatory/programmatic requirements. Most participants expressed interest in low-threshold treatment. Conclusions: Existing treatment barriers may be addressed by shifting to lower-threshold intake processes and/or outreach-based delivery of opioid agonist treatment. Engaging PWUD in efforts to create lower-threshold treatment programs is necessary to ensure that needs are met.